Letter: the relationship between Helicobacter pylori and coronary heart disease. Issue 10 (27th April 2020) - Zhang, Chao; Li, Ningfeng; An, Yi
Abstract : LINKED CONTENT This article is linked to Rajilic‐Stojanovic et al paper. To view this article, visit https://doi.org/10.1111/apt.15650 .